Mental Health and Healthy Habits in University Students: A Comparative Associative Study - José Antonio Ruiz-Hernández; Ángela Guillén; David Pina; Esteban Puente-López (MDPI AG, 2022)
There is evidence of increased psychopathology in university students and its relationship with unhealthy lifestyle habits. The objective of this work is to examine the prevalence and differences in psychopathological symptoms and lifestyle in a sample of university students according to educational levels and area of knowledge. A comparative associative study was conducted with 1405 university students. The results indicated significant differences in psychopathology and habits in the different groups. The prevalence of psychopathology found was high, especially depressive and anxious pathologies. This incidence tends to be higher in undergraduates and/or Arts and Humanities, coinciding with those who tend to have poorer lifestyle habits. The promising contributions from this study facilitate the early detection of university students with a risk profile for the appearance or exacerbation of psychopathology, as well as the design of psychological intervention programs aimed at the psychological well-being of this population.